Heteroleptic Metal Complexes of a Pyrimidine Based Schiff Base Ligand Synthesis, Characterization and Biological Activity - D. T. Sakhare (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
In this work, heterocyclic Schiff bases ligands derived from 2-amino-4,6-dimethylpyrimidine with 2-hydroxy-4-bromobenzaldehyde (L₁) was synthesized. These ligand used to synthesis complexes of Fe(III), Ni(II), Co(II), and Cu(II). The synthesized compounds have been characterized by FT-IR, 1H-NMR and UV-Vis techniques for the ligands and FT-IR, UV-Vis, all reactions monitored by TLC, molar conductivity and magnetic susceptibility measurements for the corresponding complexes. General formula of complexes are [Cu(L1)2(H2O)2], [Co(L1)2(H2O)2], [Ni(L1)2(H2O)2], [Fe(L1)2Cl2]Cl. All complexes are paramagnetic. The results of the molar conductivity measurements indicated that all complexes are non-electrolytes in (DMF) except the complexe [Fe(L1)2Cl2]Cl is electrolyte with a molar ratio (1:1). An octahedral geometry for all the complexes of. The ligands are bidentate, (L₁) through phenolic (OH) and azomethine nitrogen. The ligand and its complexes were screened for their antifungal and antibacterial activity against Aspergillus niger, Penicillium chrysogenum, Fusarium moneliforme and Aspergllus flavus .and Escherichia coli, Salmonella typhi, Staphylococcus aureus, B. subtilis. The result indicated that the complexes exhibited good antifungal and antibacterial activities.